Por uma ciência da linguagem no/do Brasil: percursos e irrupções teóricas - Ruiz, Marco Antonio Almeida (2019)
For a long time, linguistics in Brazil developed, basically, from reflections undertaken from european and north american theoretical models, whose objective was to choose (or import) a certain vision about the language and apply it over data in brazilian portuguese. Currently, our linguistics – Brazil’s linguistics – perhaps more mature and established, count on its own models that take language as object of its reflection. So, it’s not about to highlight one theory or another, raising its positive or negative aspects, but to recognize that brazilian researchers drank from foreigner wells, adapting and utilizing whatever good they found in the best way possible. In a scientific paper, whose title is Uma teoria brasileira do idioma, published in the magazine Língua Portuguesa, on April 2012, Módolo and Braga wrote about some linguistic theories developed by brazilians knowledged in our last years’ territory. The authors highlight, e.g., the Gramática construtural da língua portuguesa from Back and Mattos (1972); the Sociolinguística paramétrica from Tarallo and Kato (1989); and the Abordagem multissistêmica from Ataliba Teixeira de Castilho (2010). Related to discourses’ field of study, we see constant reformulations and theoretical propositions that can be thought of in the brazilian way, such as the Semiótica da canção (Semiotics of the song), proposed by Luiz Tatit (2007); the Teoria do silêncio (Silence theory), from Eni Orlandi (2007); the Semântica do Acontecimento (Event Semantic), proposed by Eduardo Guimarães (2005); and the Teoria dos estereótipos básicos e opostos (Basic and Opposing stereotypes theory) from Sírio Possenti (2010). As an effect, such theories build their own theoretical objects differently, although taking discourse as object of observation. To this Ph.D. research, we understand discourse studies as a group of disciplines that has language, overlapped in its different orders (linguistics, enunciatives, historical) and expressed in distinct materialities (verbal, visual, verbal-visual), as an object of study. This way, based on theoretical assumptions from french discourse analysis, mainly on the thoughts about the notion of discourse event and narrative event, from Jacques Guilhaumou (2009), we have as objective to investigate the writing of discourse analysis’ history in our country, considering its different aspects and the different discourse flows that developed in our scenario after its reception and institutionalization in 1980, constituting it through a heterogeneous research network capable of composing a singular field, the discourse Studies. Thus, our corpus is composed of three brazilian discourse theory work, which are: Humor, língua e discurso (2010) from Sírio Possenti; Ironia em perspectiva polifônica (2008) from Beth Brait; and As formas do silêncio: no movimento dos sentidos (2007) from Eni Orlandi. Such narratives, beyond (re)visiting foreigner theories, aim towards providing new research methodologies from new angles’ perspectives, promoting reflections about the way of doing science itself – metadiscoursive event – and a particular way for brazilian discourse analysis.